Complete revascularization determined by myocardial perfusion imaging could improve the outcomes of patients with stable coronary artery disease, compared with incomplete revascularization and no revascularization - Li, Jiehui; Yang, Xiubin; Tian, Yueqin; Wei, Hongxing; Hacker, Marcus; Li, Xiang; Zhang, Xiaoli (Journal of nuclear cardiology, 2019)
To compare the outcomes among patients treated by complete coronary revascularization (CCR) or incomplete coronary revascularization (ICR) and no coronary revascularization (NCR) by myocardial perfusion imaging (MPI), as well as to evaluate the impact of severity of ischemia on patients with coronary artery disease (CAD) by different therapy strategies. Using myocardial ischemia severity determined by MPI guiding treatment strategies for CAD patients still lacks strong clinical evidences. Consecutive patients (N = 286) underwent clinical stress-rest SPECT MPI and were retrospectively followed-up. For assessment of outcome of treatment, all patients were classified into three groups (CCR, ICR, and NCR), and further divided into two subgroups as mild ischemia (< 10% ischemic myocardium) and moderate-severe ischemia (≥ 10% ischemic myocardium). All-cause death was defined as the primary endpoint, and the composite of deaths, nonfatal myocardial infarction, and repeat revascularization (MACE) as the secondary endpoint. Two-hundred eighty-six patients were followed-up for 46 ± 21 months. Thirty deaths and 65 MACEs were recorded. Patients treated by revascularization had significantly lower MACE (P < .001) but not mortality (P = .158) than patients treated by NCR. Outcomes of CCR related to mortality rate were greater than ICR and NCR (death: P = .019, MACE: P < .001). In patients with moderate-severe ischemia, CCR showed improved outcomes than ICR and NCR (death: P = .034; and MACE: P < .001). In patients with mild ischemia, the outcomes of CCR, ICR, and NCR had no significant difference (P > .05). Multivariate regression Cox analysis revealed that summed difference score [death: HR 1.09 (1.03, 1.15), P = .004] was an independent risk factor and CCR was an independent negative predictor [death: HR 0.31 (0.12, 0.81), P = .017; MACE: HR 0.30 (0.16, 0.57), P < .001]. Outcomes of patients treated by CCR were most likely more promising in comparison with treatment of ICR and NCR, especially when patients had over 10% ischemic myocardium.